An Internet-Based Tailored Hearing Protection Intervention for Firefighters: Development Process and Users' Feedback. Issue 4 (July 2013) - Hong, OiSaeng; Eakin, Brenda L.; Chin, Dal Lae; Feld, Jamie; Vogel, Stephen
Background . Noise-induced hearing loss is a significant occupational injury for firefighters exposed to intermittent noise on the job. It is important to educate firefighters about using hearing protection devices whenever they are exposed to loud noise. Computer technology is a relatively new health education approach and can be useful for tailoring specific aspects of behavioral change training. The purpose of this study is to present the development process of an Internet-based tailored intervention program and to assess its efficacy. Method . The intervention programs were implemented for 372 firefighters (mean age = 44 years, Caucasian = 82%, male = 95%) in three states (California, Illinois, and Indiana). The efficacy was assessed from firefighters' feedback through an Internet-based survey. Results . A multimedia Internet-based training program was developed through (a) determining program content and writing scripts, (b) developing decision-making algorithms for tailoring, (c) graphic design and audio and video productions, (d) creating computer software and a database, and (e) postproduction quality control and pilot testing. Participant feedback regarding the training has been very positive. Participants reported that they liked completing the training via computer (83%) and also that the Internet-based training program was well organized (97%), easy to use (97%), and effective (98%) and held their interest (79%). Almost all (95%) would recommend this Internet training program to other firefighters. Conclusion . Interactive multimedia computer technology using the Internet was a feasible mode of delivery for a hearing protection intervention among firefighters. Participants' favorable feedback strongly supports the continued utilization of this approach for designing and developing interventions to promote healthy behaviors.